Answer:
k = 3.
Step-by-step explanation:
By the Factor Theorem. if x+a is a factor of f(x) then f(-a) = 0.
Here we use f(-1):
f(-1) = (-1)^3 + 2(-1) + k = 0
-1 - 2 + k = 0
k = 3.
8/12 and 4/6 and10/15 and20/30 and 40/60
As a disclaimer, I can't say I'm completely confident in this answer. Use at own risk.
Formulas:
Year 1: 328,000 (sales) - 117,000 (expense) = 211,000 (profit)
Year 2: 565,000 (sales) - x (expense) = y (profit)
Net Profit: 211,000 + y = 113,000
Math
211,000 (profit y1) + 565,000 (sales y2) = 776,000
776,000 - 113,000 (net profit) = -663,000 (expenses)
Confirm:
Net Profit: 211,000 + y = 113,000 (listed in formulas, just a reminder)
Plug in: 565,000 (y2 sales) - 663,000 (our solution) = -98,000
211,000 (y1 net) + -98,000 (our plug in) = 113,000 (2 year net profit given to us)
9514 1404 393
Answer:
5√5
Step-by-step explanation:
Use the distance formula:
d = √((x2 -x1)² +(y2 -y1)²)
d = √((-7-(-2))² +(-7-3)²) = √((-5)² +(-10)²) = √(25 +100)
d = √125 = √(25·5)
d = 5√5 . . . . distance between the points